Comparative analyses of fundamental differences in membrane transport capabilities in prokaryotes and eukaryotes. - Qinghu Ren; Ian T Paulsen (PLoS Computational Biology, 2005)
Whole-genome transporter analyses have been conducted on 141 organisms whose complete genome sequences are available. For each organism, the complete set of membrane transport systems was identified with predicted functions, and classified into protein families based on the transporter classification system. Organisms with larger genome sizes generally possessed a relatively greater number of transport systems. In prokaryotes and unicellular eukaryotes, the significant factor in the increase in transporter content with genome size was a greater diversity of transporter types. In contrast, in multicellular eukaryotes, greater number of paralogs in specific transporter families was the more important factor in the increase in transporter content with genome size. Both eukaryotic and prokaryotic intracellular pathogens and endosymbionts exhibited markedly limited transport capabilities. Hierarchical clustering of phylogenetic profiles of transporter families, derived from the presence or absence of a certain transporter family, showed that clustering patterns of organisms were correlated to both their evolutionary history and their overall physiology and lifestyles.